Exploring Self-Awareness as a Predictor of Character Education Values among Pre-Service Elementary Islamic Teachers - Devi Wahyu Ertanti; Ika Anggraheni (AL-ISHLAH: Jurnal Pendidikan, 2025)
The need for effective character education in Indonesia places pre-service teachers at the forefront of moral development in schools. However, the internal psychological factors that support character formation—such as self-awareness—remain underexplored in Islamic teacher education contexts. This quantitative study examined the predictive role of self-awareness on character education values among 280 sixth-semester students in the Islamic Elementary Teacher Education Program at Universitas Islam Malang. Data were collected using a 45-item Likert-scale questionnaire measuring four dimensions of self-awareness and five core character values. Analyses included descriptive statistics, assumption testing, and both simple and multiple linear regression. Findings show that self-awareness significantly predicts character education values, with simple regression explaining 42.2% of variance (R² = 0.422), and multiple regression across the four dimensions accounting for 55.1% (R² = 0.551). The most influential predictors were self-reflection and emotional regulation, followed by emotional self-awareness, awareness of strengths and weaknesses, and social self-awareness. Descriptive data indicated high levels of both self-awareness and character values among participants. These results underscore self-awareness as a critical internal factor shaping pre-service teachers’ capacity to embody and model character values. The findings advocate for integrating reflective and emotional regulation training into teacher education curricula to better prepare future educators as moral exemplars in the classroom.